2023
DOI: 10.1007/s13555-023-00889-0
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia Universalis in an Adolescent Successfully Treated with Upadacitinib—A Case Report and Review of the Literature on the Use of JAK Inhibitors in Pediatric Alopecia Areata

Abstract: Alopecia areata (AA) is a cell-mediated autoimmune disease in which a cytotoxic T-cell response against hair follicles occurs. AA has been demonstrated to frequently co-exist with atopic dermatitis (AD), and the coincidence of atopy predisposes to a more severe course of the disease. To date, therapeutic options in AA, especially in the pediatric population, are mainly limited to corticosteroids, irritants, sensitizers, and immunosuppressive agents. Recently, innovative therapies have emerged, among which Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…However, Patient 4's SALT score showed significant improvement after three months of medication compared to the baseline period. (16)(17)(18). Improvement in both atopic dermatitis and AA has been reported in patients with concurrent atopic dermatitis and AA using Upadacitinib.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, Patient 4's SALT score showed significant improvement after three months of medication compared to the baseline period. (16)(17)(18). Improvement in both atopic dermatitis and AA has been reported in patients with concurrent atopic dermatitis and AA using Upadacitinib.…”
Section: Discussionmentioning
confidence: 94%
“…No adverse safety events were observed during or after the treatment. 16 In a retrospective case study of patients with alopecia areata, it was found that alopecia areata significantly improved in all three adult patients after 3-8 months of oral Upadacitinib. 17 18 Based on reported cases and studies to date, Upadacitinib has a dual therapeutic effect in patients with atopic dermatitis and alopecia areata.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A drug used in dermatology for the treatment of atopic dermatitis. Several cases of improvement in patients with alopecia areata treated with upadacitinib for atopic dermatitis have been reported so far [81][82][83][84][85]. Upadacitinib be considered (similarly to dupilumab) for the treatment of children over 12 years of age with alopecia areata coexisting with atopic dermatitis because of studies confirming safety in patients between 12 and 18 years of age [86].…”
Section: Upadacitinib (Jak 1 Inhibitor)mentioning
confidence: 99%
“…Lek stosowany jest w dermatologii do leczenia atopowego zapalenia skóry. Dotychczas opisano kilka przypadków uzyskania poprawy u pacjentów z łysieniem plackowatym leczonych upadacytynibem z powodu atopowego zapalenia skóry [81][82][83][84][85]. Lek może być rozważany (obok dupilumabu) do leczenia dzieci powyżej 12. roku życia z łysieniem plackowatym współistniejącym z atopowym zapaleniem skóry z uwagi na potencjalną skuteczność i badania potwierdzające bezpieczeństwo u pacjentów między 12. a 18. roku życia [86].…”
Section: Upadacytynib (Inhibitor Jak 1)unclassified